Nilai-nilai Pendidik dalam Perspektif KH. M. Adnan Syarif - Faiqotul Maghfiroh; Haidar Idris (Moderasi : Journal of Islamic Studies, 2021)
This research is based on education in Indonesia, which is considered very rigid, bureaucratic and feels like nothing and futile. Problems in the world of education cannot be separated from the role of educators and a leader in an educational institution or foundation. This research is focused on the values ​​of educators from the perspective of KH. M. Adnan Syarif and the relevance of KH's example. M. Adnan Syarif in the book For the sake of Islam and NU: Commemorating the Actions and Struggles of KH. M. Adnan Syarif and aims to find out the values ​​of educators and the relevance of the example of a Kiai as an educator figure in an Islamic boarding school-based educational institution or foundation. This study uses the Literacy Study method (library research) which uses Content Analysis data collection techniques by reviewing books, and scientific works related to the focused problem. The primary data source in this research is the book “For the sake of Islam and NU: Memorizing the Actions and Struggles of KH. M. Adnan Syarif” which focuses on the values ​​of educators and their relevance by using a descriptive analysis approach. The results of the study show that the values ​​of KH. M. Adnan Syarif, namely the value of high dedication, professional, visionary, productive and intellectual. The values ​​of educators in the perspective of KH. M. Adnan Syarif is relevant to the competence of teachers and the opinions of several experts.